COMPREHENSIVE MODERNIZATION OF BOGIES 18-100 TO REDUCE WHEEL WEAR AND IMPROVE RIDE QUALITY OF FREIGHT CARS - Gregg Hansen, W. M.; Lashko, O. D.; Ushkalov, V. F.; Mokryi, T. F.; Malysheva, I. Yu.; Mashchienko, I. A. (Science and Transport Progress, 2004)
Based on theoretical and experimental studies, combined retrofit of standard (18-100) freight-car trucks is proposed. This retrofit makes it possible to increase the maximum running speed by 30 to 40 km/h, to extend the service life of damping system elements of bolster suspension by a factor of 5 to 10, to reduce substantially the center plate arrangement wear intensity, to decrease the wheel flange wear nearly by a factor of 2, to reduce traction power consumption by decreasing the wheel/rail interaction.